Medicolegal model for time of death of a homicide victim using computational approach - Amadi, U. C. (International Journal of Mathematical Analysis and Modelling, 2026)
The study explores the medicolegal model for time of death of a homicide victim using computational approach. Matlab software using Runge-kutta ODE45 numerical scheme was used to simulate the results output which was analyzed as well. Three statements of problem were studied computationally and various time of death were predicted using step size h = 1, h = 0.1 and h = 0.01. The decaying rate parameter which was used in the construction of the predictive model equations for the four three statements of problem were computed as well with the values of beta1, beta2, beta3 and beta4 being stated as 0.0028, 0.6931, 0.1335, and 0.2877 respectively. The study achieved the following results: construction of predictive model equation for various statements of homicide victims’ cases using secondary data, computation of the various decaying rate parameters, predictions of the time of dead using computational method.